Enhancement of Charge Transfer in Quantum Dot–sensitized Solar Cell Photoanodes by Supporting rGO Layers - Dang Huu Phuc; Ha Thanh Tung; Le Doan Duy; Le Minh Nhan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
In this study, we have studied and fabricated quantum dot sensitized solar cells based on photoanodes with the support of rGO buffer layer to enhance the electron transfer ability from TiO2 nano-semiconductor to FTO substrate. The rGO materials were fabricated by hydrothermal method, then they were coated on FTO substrate by Screen - Printing technique to create rGO nano films. The thickness of rGO films was studied from 1 to 3 layers to evaluate the mobility of charge, reduce recombination and resistance of film. Experimental results were determined by structural properties using XRD, FTIR, EDX and XPS, FESEM spectra; determined optical properties using UV-Vis absorption and transmission spectra; determined optical, electrical and chemical properties using Nyquist and EIS spectra. The maximum measured efficiency was 5.23% for the FTO/rGO(2)/TiO2/QDs film, current density 21.34 mA/cm2, open circuit voltage 5.525V and fill factor of 0.34. These results were also proven through the research results of optical properties, electrochemical properties. In addition, these results are also consistent with the studies of others. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).